Aktualisasi Program Projek Penguatan Profil Pelajar Pancasila dan Profil Pelajar Rahmatan Lil Alamin di MI Salafiyah Bangilan Falah - Muzakki, Ahmad; Afida, Febrian Nafisa Nurul; Ulfiah, Ulfiah (Madrasah Ibtidaiyah Education Journal, 2024)
As an effort to build student characteristics, this is by implementing a project to strengthen the Pancasila student profile and student profilerahmatan night alamin (P5-P2RA) for MI Salafiyah Bangilan students. It is hoped that with this project students will get the opportunity to learn and develop the positive qualities needed to become good citizens, especially discipline and responsibility. The purpose of writing this article is to find out how effective these two profiles are. Data collected through observation, observation and understanding from various reference sources is a qualitative method in this research. From the results of research conducted on students at MI Salafiyah Bangilan, it shows that through the Project for Strengthening the Pancasila Student Profile and Student ProfileRahmatan night Alamin (P5-P2RA) can form disciplined and responsible behavior in MI Salafiyah Bangilan students, because they have the opportunity to learn the values ​​or norms of Pancasila andrahmatan night alamin and apply it in the social environment in everyday life.